2018
DOI: 10.3389/fphys.2018.01604
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Meta-Analysis of the Associations Between MicroRNA Polymorphisms and Susceptibility to Rheumatoid Arthritis

Abstract: Aims: Rheumatoid arthritis (RA) is characterized by cartilage and bone damage leading to disability. Here, the association between microRNA (miRNA) polymorphisms and susceptibility to RA was evaluated by performing an updated meta-analysis and systematic review.Main methods: An electronic search of databases including PubMed and Embase was performed from inception to December 8, 2017 to retrieve studies investigating the association between miRNA polymorphisms and RA risk. Two reviewers independently screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…A novel approach employing -omics tools is measuring micro-(small non-coding) RNA’s, which can bind to mRNA, thereby influencing gene expression. However, limited data to disease relevance are available, though susceptibility to RA was shown in a meta-analysis [ 299 ], and their potential role for other diseases, such as neurodegenerative ones an the related interplay to OS have been reviewed [ 300 ].…”
Section: Markers Of Os Relation To Disease and Practical Aspectsmentioning
confidence: 99%
“…A novel approach employing -omics tools is measuring micro-(small non-coding) RNA’s, which can bind to mRNA, thereby influencing gene expression. However, limited data to disease relevance are available, though susceptibility to RA was shown in a meta-analysis [ 299 ], and their potential role for other diseases, such as neurodegenerative ones an the related interplay to OS have been reviewed [ 300 ].…”
Section: Markers Of Os Relation To Disease and Practical Aspectsmentioning
confidence: 99%
“…SNPs in the miRNA binding sites can alter miRNA-mRNA binding affinity, which alters expression of the corresponding genes, thereby affecting cell proliferation, apoptosis and development. This process is associated with susceptibility to diseases, including cancer and autoimmune diseases (20,28,29). Here, SNP rs16917496 in the miR-502 binding site of the 3'-UTR of SET8 mRNA was associated with the occurrence of RA; low SET8 and higher ROS levels and decreased IL-10 expression were associated with CC genotype and increased risk of RA.…”
Section: Discussionmentioning
confidence: 91%
“…In a further study on the same SNP rs3746444 conducted on Han Chinese [22], there was no association when tested; however, the finding indicated that CT genotype increases the level of anti-CCP antibody which increases the risk of RA. Other studies showed a variation in associations; for example, in [21] Zhou et. al.…”
Section: Discussionmentioning
confidence: 97%